The funny stuff : the official P.J. O'Rourke quotationary and riffapedia - O'Rourke, P. J. (Atlantic Monthly Press, 2022)
"When The Penguin Dictionary of Modern Humorous Quotations was published in 1987, P. J. O'Rourke had more entries than any living writer. And he kept writing funny stuff for another thirty-five years. Now, for the first time, P.J.'s best quips and riffs have been collected in one volume, edited by his longtime friend and award-winning magazine editor Terry McDonell. The Funny Stuff is organized by subject in alphabetical order from Agriculture to Xenophobia and on topics ranging from Government ("Giving money and power to politicians is like giving car keys and whiskey to teenage boys") to Apps ("we need a no-app app--let's call it a napp") to Fishing ("a sport invented by insects and you are the bait"). Throughout his fifty-year career--from his earliest days at the National Lampoon in the 1970s to his classic reporting for Rolling Stone in the '80s and '90s, and his post-Trump, pandemic, new media observations of recent years--P.J. produced incisive, amusing copy. Not only did he write memorable one-liners on the Founding Fathers, cobra blood, psychedelic drugs, social security, Chicken Little, elections, and coonskin caps, he also meticulously constructed riffs that built to a crescendo of hilarity and outrage and are still being quoted years later. Armed with his singular, acerbic voice, P.J. writes with the electric verbal energy of Tom Wolfe and Hunter S. Thompson; he's just more flat-out funny. And through it all comes his clear-eyed take on politics, economics, human nature--and fun. The Funny Stuff is a book for P.J. fans to devour but also a book that will bring new readers, standing as testament to one of the truly original American writers of the last fifty years"--